Unusual Paraneoplastic Presentation of Cholangiocarcinoma - Aman Opneja; Sonia Mahajan; Sargam Kapoor; Shanthi Marur; Steve Hoseong Yang; Rebecca Manno (Case Reports in Medicine)
Introduction. Cutaneous paraneoplastic syndromes are a heterogeneous group of skin manifestations that occur in relation to many known malignancies. Paraneoplastic occurrence of SCLE has been noted but is not commonly reported. SCLE association with cholangiocarcinoma is rare. Case Presentation. A 72-year-old man with a history of extrahepatic stage IV cholangiocarcinoma presented with a pruritic rash. Cholangiocarcinoma had been diagnosed three years earlier and was treated. Five months after interruption of his chemotherapy due to a semiurgent surgery, he presented with explosive onset of a new pruritic rash, arthralgias, and lower extremity edema. Physical exam revealed a scaly erythematous rash on his arms, hands, face, neck, legs, and trunk. It was thick and scaly on sun exposed areas. Skin biopsy revealed vacuolar interface dermatitis. Immunofluorescence revealed IgM positive cytoid bodies scattered along the epidermal basement membrane zone. PET-CT scanning revealed metabolically active recurrent disease in peripancreatic and periportal region with hypermetabolic lymph nodes. Oral steroids and new regimen of chemotherapy were started. Rash improved and steroids were tapered off. Discussion. Paraneoplastic syndromes demonstrate the complex interaction between the immune system and cancer. Treatment resistant SCLE should raise a suspicion for paraneoplastic etiology.